Impact of leadership approaches and appraisal practices on hospital workforce and environment - Satheesh, Subodh S.; Cholleti, Anila (Intelektual Pustaka Media Utama, 2025)
Hospital appraisal practices can directly impact workforce-based outcomes, including work performance, retention rate, and physical and emotional well-being. This study aimed to evaluate the effectiveness of performance appraisals and leadership approaches on the overall job satisfaction of the workforce in healthcare settings. A descriptive cross-sectional method was employed to collect data from 258 randomly selected health workforce from different private hospitals in Bangalore, India. A structured questionnaire was used to evaluate the appraisal process, leadership approaches, and sentiments. SPSS version 26 and Python 3.13 were used for statistical analysis. Most of the participants (62.2%) had a good understanding of the performance appraisal process, viewing it as essential for professional growth (95%) and work quality (96.5%). However, 53.8% felt that appraisal requirements were poorly communicated, with 58.9% reporting common unfair practices. Over half of them (56.3%) acknowledged their manager's influence, but only 43.6% expressed moderate satisfaction. This study found that despite the good understanding of the performance appraisal among the study participants, the lack of communication and the unethical work environment contributed to dissatisfaction. Thus, organizations should develop a more transparent, fair, and employee-centric appraisal system to enhance job satisfaction, workforce stability, and overall patient care quality.